Sub-Wavelength Probing and Modification of Complex Photonic Structures - Vignolini, Silvia (Premio Tesi di Dottorato, 2010)
The aim of this thesis consists in the study and modification of complex photonic nano-structures. Nowadays, propagation of light in such materials is a rich and fascinating area of research, both for its fundamental implications and for its practical technological impact. To deeply investigate light propagation inside these structures a high spatial resolution technique is required, especially because intriguing effects often occur on length scales comparable with the diffraction-limit or involve coupling phenomena on this length scale. For this reason in this thesis a Scanning Near-Field Optical Microscope represents one the most straightforward tool both to study and locally modify complex photonic nano-structures from perfect periodic to completely random ones.